PERAN SYARIAT POLIGAMI DALAM MENGATASI PROBLEMATIKA HIDUP WANITA PASCA PERCERAIAN DAN KEMATIAN SUAMI - Muhammad Nurul Fahmi; Winning Son Ashari; Sucipto (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
A marriage has an important role for human in realizing their happiness. Marriages that are permitted by the Shari'a are not only monogamous, but also polygamous. However, polygamy often gets a negative stigma from some circles, including as one of the triggers for divorce. Women who no longer have husbands (widows), either because of divorce or death, have to face various difficult life problems. Therefore, it is necessary to find a solution to the widows’ problems. Despite getting a negative stigma, polygamy should be a solution to the problems of widows' lives. From these problems, the researchers want to know the concept of polygamy according to Islamic Law, the problems of womans’ life after divorce and the death of their husband, and the role of polygamy in resolving them. In collecting data, the researchers used a qualitative approach with literature study techniques and then analyzed it using a descriptive method. The results of this study are: 1) Polygamy in Islam must follow the provisions: able to provide physical and spiritual support, a maximum of 4 wives at a time, able to be fair, and not marrying two women who are close in lineage; 2) Women's life problems after a divorce or the death of their husband include: domestic problems, economic problems, and psychological problems. 3) The application of a healthy polygamy based on the Shari'a is able to overcome the problems of women's life after divorce and husband's death. Therefore, women who are widowed can be reduced and the problems of their lives can be resolved.